The Role Of Culture In Prescribing Beliefs And Practices For Achieving Success Chinese Versus Javanese Managers In Indonesia - Sunaryo, Lenny (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2010)
This study is based on an exploratory empirical study (carried out in 2004-2005) investigating the impact of Chinese social institutions (guanxi and wulun) to managerial values and business practices for achieving success in organizational settings. The study tries to fnd answer behind the enduring history of the economic success of Chinese people in Indonesia. It follows Reddings suggestion that Confucianism is a key root cause of the economic success of overseas Chinese, including those in Indonesia. The study explores managerial values and business practices in Chinese-managed organizations as compared to Javanese-managed organizations. The study is also intended to construct factors representing managerial values and business practices that prevail in Indonesia. Research fndings show there is only one variable that signifcantly diferentiate Chinese and Javanese managerial values in Indonesia. This single variable may be helpful for enhancing our understanding of managerial values and business practices n the socio-cultural perspectives that prevail in Indonesia, and that it may be used for future research to build dimensionality of business cultures and management practices in diferent contexts.